Relation between Weighted Mean Matrices and Area of Application and Challenges - Kumar, Nand Kishor; Mahato, Raj Kumar (Journal of Business and Social Sciences, 2024)
This paper established relationship between (N, pn) and (N, qn) weighted mean matrices, for lp spaces as 1 < p < ∞). This paper also contains its components, applications and Challenges and Considerations. A flexible tool that considers the importance of individual data points, weighted mean matrices provide more in-depth data analysis. For the purpose of making well-informed judgments based on weighted averages, they find applications in a variety of fields, including environmental science and finance. Weighted mean matrices can shed light on complicated data sets when used correctly.